2023
DOI: 10.3390/children10010119
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedics and Trauma in Children: Key Problems and Future Insights

Abstract: Orthopedic disorders among children are frequently encountered in clinical practice [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Finally, regarding maternal occupation, most mothers in the study group (87.7%) and control group (73.4%) were working mothers. Figure (1) illustrates that the highest percentage of mothers live in rural areas in n the study and control groups (60%, and 76.7%, respectively). Table (2) clarified that more than twofifths (43.3%) of the children in The study and control groups were between the ages of 4 and 5 years.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Finally, regarding maternal occupation, most mothers in the study group (87.7%) and control group (73.4%) were working mothers. Figure (1) illustrates that the highest percentage of mothers live in rural areas in n the study and control groups (60%, and 76.7%, respectively). Table (2) clarified that more than twofifths (43.3%) of the children in The study and control groups were between the ages of 4 and 5 years.…”
Section: Resultsmentioning
confidence: 93%
“…Table (1) showed that 40% of the mothers in both groups were 25-30 years old. Furthermore, regarding the mother's educational level, half (50%) of the mothers in the study group were illiterate, whereas 36.7% of mothers in the control group had basic education.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…There are different types of traumata, including vascular trauma (24), spinal trauma (25), orthopedic trauma (26), and TBI (27).…”
Section: Discussionmentioning
confidence: 99%